Jugoszlávia felbomlásának interpretációi a nyugati szakirodalomban - Juhász, József (Közép-Európai Közlemények, 2011)
The breakup of Yugoslavia was an important and tragic chapter of European history in the 1990s, and has gained the attention of many historians and social scientists. It is therefore no wonder that today the literature on the subject is vast. Neither is it surprising that this literature is hardly homogeneous: their description of events varies on both the quality of the analysis but more importantly on the key explanation they employ. These support and complement each other on some points, but also often debate one another on others. This paper attempts to give an overview of these alternative theories that have been formulated in the Western academic literature. These are: the theory of cultural determinism, those emphasizing the ambitions of the Great Powers, the neoliberal narrative, and the self-determination paradigm. The main reason for the dissolution as identified by the respective authors was used as the basis for categorization. A typical book or paper shall also be presented to illustrate each theory.